Maira Valley (Piedmont): a territorial laboratory of a new mountain population - Giacomo Pettenati (Revue de Géographie Alpine)
The western sector of Italian Alps, since the ‘80s, has been experiencing a re-population process after a long period of social, cultural and economic isolation due to a long emigration process. An increasing number of households and individual citizens are moving from urban areas and lowlands to mountain areas where they set up innovative businesses and develop personal projects. The present article seeks to investigate the roles that the new inhabitants play at a social and economic level in the Maira Valley. For the importance and the scale of the phenomenon, the Maira Valley is considered a particularly interesting “territorial laboratory”, as confirmed by the results of two researches conducted between 2008 and 2013. The interviews to 36 new inhabitants of the area showed that they have a particularly strong relationships with the territory because the territory itself is at the core of their life projects. As a consequence, many areas of the valley – previously affected by depopulation and no longer able to serve their functions - repopulated thus countering the process of social and economic marginalization. At the same time, the research shows the need for targeted policies to support the trend, make it sustainable over time and able to reshape local dynamics.